Pengaruh Kebocoran Palka terhadap Kualitas Muatan Nikel Serta Kinerja Operasional Kapal MV. Lumoso Aman - Firgian Nasih; Kuncowati Kuncowati; Elva Febriana Anggreany (Indonesian Maritime Researchers and Lecturers, 2026)
Hatch cover leakage is a significant problem on bulk carrier vessels, as seawater ingress into cargo holds can increase the moisture content of nickel ore cargo, reduce cargo quality, and disrupt ship operations. This condition may also increase the risk of cargo liquefaction, delay cargo handling processes, and cause operational losses. This study aims to analyze the impact of hatch cover leakage on nickel ore cargo quality, identify the technical factors causing leakage, and evaluate preventive and corrective measures implemented on MV. Lumoso Aman. This research used a qualitative descriptive method. Data were collected through direct observation of cargo hold conditions and ship operations, semi-structured interviews with the Chief Officer and Third Officer., documentation, and literature review. Data analysis involved data collection, reduction, presentation, and conclusion drawing, with validity ensured through source, technique, and time triangulation. The results show that hatch cover leakage was caused by damaged rubber packing, corrosion of hatch cover components, drainage system problems, and insufficient maintenance and inspection procedures. Leakage increased moisture levels in parts of the nickel ore cargo, causing wet and lumpy conditions that reduced cargo quality and affected cargo handling efficiency. Corrective measures included regular hatch cover inspections, replacement of damaged packing, welding repairs, drainage cleaning, and implementation of preventive maintenance programs. These actions are essential to maintain cargo hold watertightness, preserve cargo quality, and support safe and efficient vessel operations.